Method for preparing activated carbon with specific adsorption of carbon dioxide

CN118458762BActive Publication Date: 2026-10-30NINGXIA HUAHUI ACTIVATED CARBON
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410559071.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-08
Publication Date
2026-10-30
Estimated Expiration
2044-05-08

AI Technical Summary

Technical Problem

为此,本申请提出一种专效吸附二氧化碳的活性炭制备方法,解决了活性炭在吸附二氧化碳后的脱附能力较差的问题,减少二氧化碳吸脱附次数,延长了吸附材料使用寿命

Benefits of technology

[0017]本发明的有益效果体现在,25%~30%的太西煤粉、5%~10%的焦煤粉、5%~15%的焦油、15%~25%的辅助粘结剂、30%~40%的竹炭粉原料质量百分比配比的原料煤,再通过炭化技术得到炭化料,再将二氧化碳与水蒸气的混合气体作为活化剂对炭化料进行2h至3h的慢速活化,得到活性炭基炭,对活性基炭进行漂洗烘干,得到活性炭;用太西煤粉掺配竹炭粉并以煤焦油作为主粘结剂,同时掺配辅助粘结剂作为孔径模板加工活性炭,同时在高温、绝氧环境的情况下,通过质量百分比为25%~35%的二氧化碳和65%~75%的水蒸气的混合气体,降低蒸汽使用量,温和活化反应强度,降低反应速度,以此对CO2的吸附量可以稳定达到55ml/g,达到提升CO2吸附效果的作用。本申请通过这种设置,解决了活性炭在吸附二氧化碳后的脱附能力较差的问题,减少二氧化碳吸脱附次数,脱附回收能耗降低30%以上,吸附材料使用寿命延长1倍。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118458762B_ABST
    Figure CN118458762B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of activated carbon for special carbon dioxide adsorption, and relates to the technical field of activated carbon preparation. The method comprises the following steps: obtaining raw coal, mixing and stirring the raw coal in proportion to obtain a mixture, adding the mixture into an activated carbon forming machine to extrude the mixture to obtain columnar material, carbonizing the columnar material to obtain carbonized material, and slowly activating the carbonized material for 2-3 hours by using a mixed gas of carbon dioxide and water vapor in a high-temperature and anaerobic environment to obtain activated carbon-based carbon. The activated carbon is rinsed and dried to obtain the activated carbon. By the method, the problem of poor desorption capacity of the activated carbon after adsorbing carbon dioxide is solved, the frequency of carbon dioxide adsorption and desorption is reduced, and the service life of the adsorption material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of activated carbon preparation technology, and in particular to a method for preparing activated carbon that is specifically effective at adsorbing carbon dioxide. Background Technology

[0002] Carbon dioxide is the most common greenhouse gas and a crucial emission indicator in environmental protection. International climate conventions have set specific limits on carbon dioxide emissions for all countries. Currently, China's carbon dioxide recovery and utilization technology is still in its early stages. Common carbon dioxide recovery technologies include solvent absorption, pressure swing adsorption (PSA), membrane separation, and catalytic combustion. However, PSA, which utilizes activated carbon adsorption technology, is the most effective method for recovering and purifying carbon dioxide. It features simple processing, high recovery efficiency, and no secondary pollution, and enjoys broad market demand.

[0003] The technology of pressure swing adsorption for carbon dioxide recovery is basically mature. However, due to the lack of high-performance activated carbon specifically designed for carbon dioxide adsorption, the technology suffers from numerous adsorption-desorption cycles, short lifespan of adsorption materials, and reduced practical effectiveness. Furthermore, it consumes a lot of energy and the adsorption effect is not ideal. Summary of the Invention

[0004] This application aims to address at least one of the technical problems existing in the prior art. To this end, this application proposes a method for preparing activated carbon specifically for adsorbing carbon dioxide, which solves the problem of poor desorption capacity of activated carbon after adsorbing carbon dioxide, reduces the number of carbon dioxide adsorption and desorption cycles, and extends the service life of the adsorption material.

[0005] This application provides a method for preparing activated carbon specifically for adsorbing carbon dioxide, comprising:

[0006] Obtain raw coal and mix it in a certain proportion to obtain a mixture;

[0007] The mixture is added to an activated carbon molding machine to extrude the mixture and obtain columnar material;

[0008] The columnar material is carbonized to obtain carbonized material;

[0009] Under high temperature and oxygen-free environment, the carbonized material is slowly activated for 2 to 3 hours by a mixed gas of carbon dioxide and water vapor to obtain activated carbon-based carbon.

[0010] The activated carbon is rinsed and dried to obtain activated carbon;

[0011] The raw coal comprises, by mass percentage: 25%–30% Taixi coal powder, 5%–10% coking coal powder, 5%–15% tar, 15%–25% auxiliary binder, and 30%–40% bamboo charcoal powder; and the mixed gas of carbon dioxide and water vapor comprises, by mass percentage: 25%–35% carbon dioxide and 65%–75% water vapor.

[0012] According to some embodiments of this application, the Taixi coal powder is obtained by grinding Taixi coal after dry distillation at 580°C to 620°C for 50 to 70 minutes.

[0013] According to some embodiments of this application, the auxiliary binder is one of phenolic residue or lignin.

[0014] According to some embodiments of this application, the carbonization of the columnar material to obtain carbonized material includes:

[0015] The columnar material is carbonized using static temperature-controlled carbonization technology to obtain carbonized material.

[0016] According to some embodiments of this application, the pore size of the activated carbon is between 0.5 nm and 1 nm.

[0017] The beneficial effects of this invention are reflected in the following: Raw coal with a mass percentage ratio of 25%–30% Taixi coal powder, 5%–10% coking coal powder, 5%–15% tar, 15%–25% auxiliary binder, and 30%–40% bamboo charcoal powder is used to obtain carbonized material through carbonization technology. Then, a mixture of carbon dioxide and water vapor is used as an activator to slowly activate the carbonized material for 2 to 3 hours to obtain activated carbon-based carbon. The activated carbon-based carbon is then rinsed and dried to obtain activated carbon. Activated carbon is processed by blending Taixi coal powder with bamboo charcoal powder and using coal tar as the main binder, while simultaneously adding an auxiliary binder as a pore size template. Furthermore, under high temperature and oxygen-free conditions, a mixture of 25%–35% carbon dioxide and 65%–75% water vapor (by mass percentage) is used to reduce steam consumption, moderate the activation reaction intensity, and slow down the reaction rate. This allows for a stable CO2 adsorption capacity of 55 ml / g, thereby enhancing the CO2 adsorption effect. This application solves the problem of poor desorption capacity of activated carbon after adsorbing carbon dioxide by adopting this setting, reduces the number of carbon dioxide adsorption and desorption cycles, reduces desorption and recovery energy consumption by more than 30%, and extends the service life of adsorption materials by 100%.

[0018] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0019] Additional aspects and advantages of this application will become apparent and readily understood in conjunction with the following description of the embodiments, in which:

[0020] Figure 1 A schematic flowchart of a method for preparing activated carbon specifically for adsorbing carbon dioxide, provided for embodiments of this application;

[0021] Figure 2 This is a schematic flowchart of a method for preparing activated carbon specifically for adsorbing carbon dioxide, provided in another embodiment of this application. Detailed Implementation

[0022] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain this application, and should not be construed as limiting this application.

[0023] In the description of this application, it should be understood that the orientation descriptions, such as up, down, front, back, left, right, etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0024] In the description of this application, the use of "first" and "second" is for the purpose of distinguishing technical features only, and should not be construed as indicating or implying relative importance or implicitly indicating the number of technical features indicated or the order of the technical features indicated.

[0025] In the description of this application, unless otherwise expressly defined, terms such as "setup," "installation," and "connection" should be interpreted broadly, and those skilled in the art can reasonably determine the specific meaning of the above terms in this application in conjunction with the specific content of the technical solution.

[0026] Carbon dioxide is the most common greenhouse gas and a crucial emission indicator in environmental protection. International climate conventions have set specific limits on carbon dioxide emissions for all countries. Currently, China's carbon dioxide recovery and utilization technology is still in its early stages. Common carbon dioxide recovery technologies include solvent absorption, pressure swing adsorption (PSA), membrane separation, and catalytic combustion. However, PSA, which utilizes activated carbon adsorption technology, is the most effective method for recovering and purifying carbon dioxide. It features simple processing, high recovery efficiency, and no secondary pollution, and enjoys broad market demand.

[0027] The technology of pressure swing adsorption for carbon dioxide recovery is basically mature. However, due to the lack of high-performance activated carbon specifically designed for carbon dioxide adsorption, the technology suffers from numerous adsorption-desorption cycles, short lifespan of adsorption materials, and reduced practical effectiveness. Furthermore, it consumes a lot of energy and the adsorption effect is not ideal.

[0028] To address the aforementioned problems, this application proposes a method for preparing activated carbon specifically for adsorbing carbon dioxide. The embodiments of this application will be further described below with reference to the accompanying drawings.

[0029] This application provides a method for preparing activated carbon specifically for adsorbing carbon dioxide, such as... Figure 1 As shown, the method includes the following steps:

[0030] Step S100: Obtain raw coal and mix it in proportion to obtain a mixture;

[0031] The raw material coal comprises the following percentages by weight: 25%–30% Taixi coal powder, 5%–10% coking coal powder, 5%–15% tar, 15%–25% auxiliary binder, and 30%–40% bamboo charcoal powder.

[0032] Step S200: The mixture is added to an activated carbon molding machine to extrude the mixture and obtain columnar material.

[0033] In this embodiment, the raw material mass percentage of the coal is: 28% Taixi coal powder, 7% coking coal powder, 10% tar, 20% auxiliary binder, and 35% bamboo charcoal powder. In other embodiments, the raw material mass percentage of the coal may also be: 25% to 30% of Taixi coal powder, 5% to 10% of coking coal powder, 5% to 15% of tar, 15% to 25% of auxiliary binder, and 30% to 40% of bamboo charcoal powder, and the sum of these percentages shall be 100%, and is not limited to the embodiments of this application.

[0034] It should be noted that by using different carbon-based materials as raw materials, the most suitable basic material with the most suitable pore structure was found through comparison. Since the diameter of CO2 molecules is small, activated carbon has a better adsorption capacity due to its micropores when used as an adsorbent material. Therefore, when selecting activated carbon, the CTC index is between 25% and 40% (i.e., the iodine value is between 620 mg / g and 850 mg / g) as the selection standard.

[0035] It is understandable that Taixi coal powder is produced by grinding Taixi coal after dry distillation at 580℃ to 620℃ for 50 to 70 minutes.

[0036] In this embodiment, Taixi coal powder is obtained by grinding Taixi coal after dry distillation at 600°C for 60 minutes; in other embodiments, Taixi coal powder can also be obtained by grinding Taixi coal after dry distillation at any temperature between 580°C and 620°C for any time between 50 minutes and 70 minutes, and is not limited to the embodiments of this application.

[0037] It is understandable that the auxiliary binder is either phenolic residue or lignin.

[0038] It should be noted that Taixi coal powder has the characteristics of three lows (low phosphorus, low ash, and low sulfur) and six highs (high calorific value, high lump coal rate, high resistivity, high chemical activity, high clean coal recovery rate, and high mechanical strength). This application uses Taixi coal as the basic raw material and conducted a series of experiments: ① The raw Taixi coal was directly activated to give it suitable adsorption properties, and then its adsorption capacity for CO2 gas was verified. The test results showed that the adsorption capacity of the activated raw coal for CO2 gas was poor, only 20.31 ml / g, which was far below the expected target. It can be seen that although the activated raw coal has a certain adsorption capacity, it is not suitable for adsorbing CO2 gas. Therefore, it is necessary to perform pore adjustment treatment or blending to improve porosity and performance. ② Columnar activated carbon was formed using Taixi coal powder as raw material. This was then used as a CO2 adsorption material to test its CO2 adsorption performance. The results showed that the columnar activated carbon made from Taixi coal powder had a certain adsorption effect on CO2 gas, and its adsorption performance was much higher than that of the product directly activated from Taixi coal, reaching an adsorption index of 32.07 ml / g. Although the columnar activated carbon had a stronger CO2 adsorption capacity than the product directly activated from Taixi coal, its adsorption effect still did not meet the expected target. Therefore, further improvements are needed. ③ The carbon production process was improved by adding a dry distillation process before grinding the Taixi coal. The Taixi coal was dry distilled at 600℃ for one hour before grinding. This process can separate some of the volatile organic compounds in the coal, making the coal purer, and can also form some pores to achieve the purpose of pore formation. The CO2 adsorption test results of the activated carbon made using this process are shown in Table 1. Table 1:

[0039] Taixi Coal 1.41% 3.89% 9.71% 85% Taixi Coal Pre-oxidation 0.72% 4.16% 2.45 89%

[0040] The table above shows that the activated carbon produced by this process has a better adsorption effect than that produced by conventional processes, reaching 37.14 ml / g. However, it still does not meet the expected effect. After a series of tests on Taixi coal, it was found that activated carbon is not easy to achieve the expected effect in CO2 adsorption. Therefore, coal blending technology was considered to test its effect. In addition, using Shenfu coal, bituminous coal, coking coal, and Xinjiang coal as raw materials, and conducting experiments with the same test parameters as Taixi coal, it was found that the product made with coking coal as the raw material performed better and was comparable to the product made with Taixi coal, with a CO2 adsorption effect of 40 ml / g. The effects of other coal types were poor, with CO2 adsorption effects concentrated at around 30 ml / g to 35 ml / g. Using "Taixi coal + bamboo charcoal powder + coking coal" as raw materials, and with certain parameters, CO2 adsorption tests were conducted, and the results are shown in Table 2. The CO2 adsorption effect can be further improved based on "Taixi coal + bamboo charcoal powder", and a high adsorption effect of 53 ml / g can be achieved, which is very close to the target of 55 ml / g. Since the hardness of bamboo charcoal powder is relatively softer than that of Taixi coal, the strength of activated carbon is also significantly reduced when bamboo charcoal powder is added. Therefore, a small amount of coking coal is added to increase the strength and improve the performance of the product.

[0041] Table 2:

[0042]

[0043]

[0044] When selecting a binder, Taixi coal powder was used as the raw material, and a certain amount of phenolic residue was added. The product was prepared using an activated carbon preparation process to form a special product. CO2 adsorption testing was conducted, and the results are shown in Table 3. The CO2 adsorption performance was found to be improved, reaching 43 ml / g, which is a significant improvement. The experiment shows that this method does indeed improve CO2 adsorption and can be further improved in the future. The addition of phenolic residue can improve the CO2 adsorption effect, but it also carries the risk of reducing strength. Therefore, it is not advisable to completely replace binders such as tar; the ratio should be appropriate. Table 3:

[0045]

[0046] Step S300: Carbonize the columnar material to obtain carbonized material.

[0047] In step S400, the carbonized material is slowly activated for 2 to 3 hours in a high-temperature, oxygen-free environment by a mixture of carbon dioxide and water vapor to obtain activated carbon-based carbon.

[0048] The mass percentage of the mixed gas of carbon dioxide and water vapor is 25%–35% carbon dioxide and 65%–75% water vapor.

[0049] In some embodiments, the mass percentage of the mixed gas of carbon dioxide and water vapor is 30% carbon dioxide and 70% water vapor.

[0050] It should be noted that the high-temperature environment refers to a temperature environment above 900℃.

[0051] It should be noted that adding carbon-containing activators with special components during the activation process can appropriately plug the pores of activated carbon with larger pores, thereby increasing the proportion of micropores. Alternatively, a slower activation gas and a gentler activation reaction rate using water vapor can be selected to reduce mesopores, transition pores, and ineffective macropores, achieving precise pore size adjustment. Water vapor is generally chosen as the activator in the activation process because it is economical and has a relatively fast reaction rate. However, this can also lead to overly rapid activation, resulting in insufficient pore size. Therefore, when preparing CO2-specific adsorption activated carbon, it is worth trying to mix a certain proportion of CO2 gas into the water vapor, as shown in Table 4, to slow down the activation rate and thus enrich the pore structure. Table 4:

[0052]

[0053] Experiments have shown that activated carbon products prepared by this method have significantly improved CO2 adsorption efficiency, which can be increased by 2 ml / g to 5 ml / g compared to conventional processes. Using "Taixi coal + coking coal + bamboo charcoal powder" as raw materials for activated carbon preparation, the product obtained by this method can achieve a CO2 adsorption efficiency of 56 ml / g, which is a very ideal result.

[0054] This method enriches the pore structure of activated carbon, creating pores suitable for accommodating CO2, thereby increasing CO2 adsorption performance to achieve the target of 55 ml / g. Experiments show that adding an appropriate concentration of CO2 to the activator effectively slows down the activation rate. The concentration affects the activation rate, but high concentrations of CO2 significantly reduce activation efficiency. Further verification of the optimal ratio is needed; currently, a CO2 content of 30% achieves good results and efficiency. The activation furnace itself contains a large amount of CO2; during normal batch production, this can be controlled by strictly controlling the oxygen content within the furnace by reducing the steam volume.

[0055] Step S500: The activated carbon is rinsed and dried to obtain activated carbon.

[0056] It should be noted that the activated carbon is rinsed thoroughly and then dried to obtain activated carbon.

[0057] It is understandable that the auxiliary binder is either phenolic residue or lignin.

[0058] Specifically, the raw materials selected for the raw coal are Taixi coal, coking coal, and bamboo charcoal powder. The selected binder is a combination of coal tar and phenolic residue, or a binder formed by a combination of coal tar and lignin. The raw coal is then mixed evenly using a stirring device. During stirring, a certain pressure is required to force the binder to mix evenly, resulting in a mixture. The mixture is then extruded to obtain columnar material. The columnar material is then slowly carbonized at low temperature using a carbonization device according to a temperature gradient, resulting in a carbonized material with a uniform structure and high basic strength. The oxygen content is strictly controlled. Under high temperature and oxygen-free environment, the carbonized material is slowly activated for 2 to 3 hours using a mixed gas of 30% carbon dioxide and 70% water vapor using an activation device to obtain activated carbon-based carbon. The water vapor content used for activation is reduced by 30%, with only 70% of the water vapor being used by mass, extending the activation time and avoiding overburning. Protective gas can be added if necessary. Finally, the activated carbon-based carbon is rinsed and dried to obtain activated carbon.

[0059] It should be noted that this application utilizes a method for preparing activated carbon specifically for adsorbing carbon dioxide. The activated carbon prepared in this way achieves a CO2 adsorption capacity of over 55 ml / g, effectively solving the problem that the existing activated carbon has a large pore structure and is not suitable for adsorbing small-molecule carbon dioxide. At the same time, it solves the problem of poor desorption capacity of activated carbon after adsorbing carbon dioxide, reducing the number of carbon dioxide adsorption and desorption cycles, reducing desorption and recovery energy consumption by more than 30%, and extending the service life of the adsorption material by 100%.

[0060] In this application, activated carbon is processed by mixing Taixi coal powder with bamboo charcoal powder and using coal tar as the main binder, while also mixing in auxiliary binders as pore size templates. Simultaneously, under high temperature and oxygen-free environment conditions, a mixed gas of 25%–35% carbon dioxide and 65%–75% water vapor by mass percentage is used to reduce the amount of steam used, gently activate the reaction intensity, and slow down the reaction rate. As a result, the CO2 adsorption capacity can be stably reached 55 ml / g, thereby improving the CO2 adsorption effect.

[0061] Understandably, referring to Figure 2 Step S300 includes, but is not limited to, the following steps:

[0062] Step S310: Carbonize the columnar material using static temperature-controlled carbonization technology to obtain carbonized material.

[0063] It should be noted that the static temperature-controlled carbonization technology used in the carbonization process allows for more thorough separation of volatile organic compounds, thereby creating more porous structures, which is more conducive to activation, making the activated carbon more porous, and further improving its CO2 adsorption capacity.

[0064] It is understandable that the pore size of activated carbon is between 0.5 nm and 1 nm.

[0065] It should be noted that, under certain conditions of activated carbon pore distribution, when the pore size of activated carbon is between 0.5 nm and 1 nm, it has a good adsorption capacity for CO2.

[0066] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0067] The above description is the preferred embodiment of this application. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of this application, and these improvements and modifications are also considered to be within the scope of protection of this application.

[0068] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.

Claims

1. A method for preparing activated carbon specifically for adsorbing carbon dioxide, characterized in that, include: Obtain raw coal and mix it in a certain proportion to obtain a mixture; The mixture is added to an activated carbon molding machine to extrude the mixture and obtain columnar material; The columnar material is carbonized to obtain carbonized material; Under high temperature and oxygen-free environment, the carbonized material is slowly activated for 2 to 3 hours by a mixed gas of carbon dioxide and water vapor to obtain activated carbon-based carbon. The activated carbon-based carbon is rinsed and dried to obtain activated carbon; The raw coal comprises, by mass percentage: 25%–30% Taixi coal powder, 5%–10% coking coal powder, 5%–15% tar, 15%–25% auxiliary binder, and 30%–40% bamboo charcoal powder; the mixed gas of carbon dioxide and water vapor comprises, by mass percentage: 25%–35% carbon dioxide and 65%–75% water vapor. The Taixi coal powder is obtained by grinding Taixi coal after dry distillation at 580℃ to 620℃ for 50 min to 70 min; the auxiliary binder is either phenolic residue or lignin; the pore size of the activated carbon is between 0.5 nm and 1 nm. The carbonization of the columnar material to obtain carbonized material includes: The columnar material is carbonized using static temperature-controlled carbonization technology to obtain carbonized material.

Citation Information

Patent Citations

  • Preparation method of active carbon for adsorbing and separating carbon dioxide

    CN105502379A